De facto refugia, ecological traps and the biogeography of anthropogenic cougar mortality in Utah. Issue 9 (30th January 2013) - Stoner, David C.; Wolfe, Michael L.; Rieth, Wendy R.; Bunnell, Kevin D.; Durham, Susan L.; Stoner, Lisa L.; Jeschke, Jonathan
Abstract Aim Modern extirpations within the Carnivora have generally followed the human footprint. The contagion hypothesis predicts that range contractions should occur along gradients in human activity, leaving relict populations in remote areas at range edges. We evaluated this hypothesis for cougars (Puma concolor), a widely distributed and heavily exploited North American carnivore. Location Colorado Plateau and Great Basin ecoregions within Utah, USA. Methods We examined the spatial distribution of anthropogenic cougar mortality (n = 4217) using indices of remoteness and habitat quality within a GIS/multiple‐regression analytical framework. To identify areas of disproportionately high or low exploitation rates, we used break‐points from the literature and local field studies. We defined de facto refugia as watersheds with mean annual harvest rates ≤ 24% of the predicted population, whereas ecological traps were those watersheds that exceeded this value. Results Cougar harvest rates were greater in the core and lower along the periphery of their statewide geographic range. The largest refugia were overrepresented in arid ecoregions with low human population densities, whereas ecological traps were concentrated in areas of low remoteness. Ecological traps were within mean cougar dispersal distances from refugia, highlighting the potential for source‐sink dynamics. Patterns of anthropogenic cougar mortality generally followed the predictions of the contagion hypothesis, being spatially correlated with human access in high‐quality habitats. Main conclusions Low‐quality habitats on the range margins are likely to harbour carnivore populations in the event of widespread human‐caused declines, and therefore may have greater conservation value than has previously been assumed. Resource managers may consider using the distribution of de facto refugia and ecological traps within a source‐sink context to develop conservation strategies for cougars and other wide‐ranging, low‐density carnivores with high dispersal tendencies.